2017
DOI: 10.3390/app7010084
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Overloading on the Reduction of Residual Stress by Cyclic Loading in Cold-Drawn Prestressing Steel Wires

Abstract: Prestressing steel wires are commonly used as reinforcement elements in structures bearing fatigue loads. These wires are obtained by a conforming process called cold drawing, where a progressive reduction of the wire diameter is produced, causing residual stress in the commercial wire. The aim of this paper is to analyze the effect of diverse in-service cyclic loading conditions (cyclic loading and cyclic loading with overload) on such a residual stress field. To achieve this goal, firstly, a numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Tanner et al [ 17 ] found that applying 2% tensile deformation to a 7010 aluminum alloy thick plate can eliminate most of the residual stress. Toribio et al [ 18 ] found that the residual stress of cold-drawn prestressing steel wires can be reduced by 90% undergoing overloads during cyclic loading, and the cause of residual stress reduction is the local constriction exerted by the plastic strain zone, which impedes the total elastic strain recovery during fatigue. The residual stress can be reduced by a certain tensile deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Tanner et al [ 17 ] found that applying 2% tensile deformation to a 7010 aluminum alloy thick plate can eliminate most of the residual stress. Toribio et al [ 18 ] found that the residual stress of cold-drawn prestressing steel wires can be reduced by 90% undergoing overloads during cyclic loading, and the cause of residual stress reduction is the local constriction exerted by the plastic strain zone, which impedes the total elastic strain recovery during fatigue. The residual stress can be reduced by a certain tensile deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The main variables affecting compressive residual stress are shown and also the limit of residual stresses [5]. In [6] it is reported that a cold-drawn prestressed wire has a significant reduction in the induced compressive residual stresses by cyclic overloading. Depending on the load which was between 0.75 and 1.25 times the yield strength the experiment shows different reduction amounts.…”
Section: Status Of Researchmentioning
confidence: 99%
“…Additional static loading could be an important factor affecting fatigue life [42,43]. A non-zero mean value of the stress is often caused by the effect of self-weight of the working element as well as the effect of initial tension in load-bearing elements (e.g., belts in gearboxes) or residual stresses [44][45][46][47]. The effectiveness of multiaxial fatigue models with life-dependent material parameters under cyclic multiaxial with zero mean stress has been validated in a few research papers [21,37,39].…”
Section: Introductionmentioning
confidence: 99%